COMMUNISTS AND THE TRADE UNION LEFT REVISITED: THE CASE OF THE UK 1964-79. (1st April 2010) - Unknown
Abstract : In the 1880s when Karl Marx lived in London and Frederick Engels worked in Manchester they wrote about the possibility of a socialist revolution in Great Britain. Much of their data collection and subsequent analysis was based on the Victorian Empire, and the class structure and struggle that emerged from the workings of capitalism in an advanced industrial state. Ever since then British communists have sought to decipher their predictions and turn them into concrete revolutionary action and organization based on a largely Leninist approach to state power and revolution. This has meant a heavy dependence on the trade unions as the mass expression of working-class solidarity and struggle, and a continuous battle with the right wing social democrats who control the minds and actions of many in the mass party of the workers, the Labour Party. This article examines the period in modern history when the CPCB came closest to realizing its revolutionary potential and program through a mixture of a left push within the labor movement at both official levels and among grass roots working class activists in the unions and elsewhere.